Proposições curriculares para a rede estadual de ensino de santa Catarina (1991-2022) e a conformação de princípios neoliberais - Minks, Catarina Aparecida Vettori (2024)
This dissertation investigates the influences contained in curricular documents Santa Catarina and the ways in which they favor the advancement of neoliberal ideals in education state public. To achieve this purpose, it analyzes guidelines originating from the policy educational reflected in curriculum documents and their implications for Basic Education through the question: What aspects are contained in the network’s curricular documents? state of Santa Catarina, from 1991 to 2022, contribute to the promotion of neoliberal principles in public education in Santa Catarina? The theoretical framework is pluralistic, based on the studies of Stephen John Ball, Martha Nussbaum and Christian Laval, among other contemporary authors, to assist in the interpretative approach as part of a dialectical logic, with elements examined in parts and then recomposed into a authorial interpretation. The method adopted is documentary research of curricular propositions Santa Catarina over the last 31 years. Data is collected through the selection of aspects relevant historical, social, political and economic contexts globally, nationally and state, relating them to Brazilian educational policies, mainly directed by the Law of Guidelines and Bases/96 (LDB/96) and by the National Common Curricular Base (BNCC) 2018. To compose the analysis, converging points are researched in the Proposals Santa Catarina Curriculums (PCSC) from 1991, 1998, 2014 and alternately are correlated the complementary updates of state curricular documents with the insertion of new ideals. The introduction serves as the first chapter and presents the difficulties faced by Basic Education in the state of Santa Catarina. The second chapter explores the Santa Catarina curricular documents with analysis of elements of their constitution, covering everything from redemocratization to the most recent changes. The third chapter analyzes the pedagogical conceptions and the underlying interferences incorporated into the Santa Catarina curriculum. The fourth chapter identifies the influence of neoliberal ideals, examining its principles and mechanisms of infiltration into educational curricula Santa Catarina. Final considerations offer insights into policy impact educational in the neoliberal context in Santa Catarina. The results reveal that the Santa Catarina curricular documents are in line with Brazilian educational policy in reason why this is defined by extrinsic agreements that permeate educational projects of globalized way. From this perspective, the Santa Catarina curricula offer pedagogical concepts distinct, maintaining the structuring axis in sociointeractionism and validating the Base Curriculum of the Santa Catarina Territory (CBTC) as a version of the national curriculum in the state context. It appears that this brings with it the language of innovation and the strengthening of advancement teaching based on skills and abilities, useful for training capable professionals, flexible and self-managed, as a contribution to technical, vocational and conformal education to marketing desires. It is concluded that the present study raises the challenge of combating aspects shaped in the state's curricular propositions and points to the conception sociointeractionist, present in the Santa Catarina curriculum, as a means to be used in favor of of a civic education with a critical and conscious sense of social and human action, apable of to include subjects and give new meaning to the role of education.